2017
DOI: 10.1091/mbc.e17-03-0134
|View full text |Cite
|
Sign up to set email alerts
|

Single and collective cell migration: the mechanics of adhesions

Abstract: Chemical and physical properties of the environment control cell proliferation, differentiation, or apoptosis in the long term. However, to be able to move and migrate through a complex three-dimensional environment, cells must quickly adapt in the short term to the physical properties of their surroundings. Interactions with the extracellular matrix (ECM) occur through focal adhesions or hemidesmosomes via the engagement of integrins with fibrillar ECM proteins. Cells also interact with their neighbors, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
279
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 308 publications
(285 citation statements)
references
References 232 publications
(255 reference statements)
3
279
0
3
Order By: Relevance
“…and cell collective migration in vivo has been reported previously. 22, 73, 74 For instance, it has been reported that lipoma preferred partner (LPP), an actin-binding protein that could degrade N-cadherin in lung cancer, could inhibit collective cell migration during lung metastasis in mice model. 75 Regarding our treatment, future studies on metastatic mice models will be performed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…and cell collective migration in vivo has been reported previously. 22, 73, 74 For instance, it has been reported that lipoma preferred partner (LPP), an actin-binding protein that could degrade N-cadherin in lung cancer, could inhibit collective cell migration during lung metastasis in mice model. 75 Regarding our treatment, future studies on metastatic mice models will be performed.…”
Section: Resultsmentioning
confidence: 99%
“…21 This process is highly dynamic and regulated by signal transduction through protein phosphorylation. 2224 Given their important roles, it is imperative to understand the signals evolved in the cytoskeleton filaments and cell-cell junctions shortly after AuNRs and PPTT stimulation for the rational design of effective strategies to inhibit cancer metastasis.…”
mentioning
confidence: 99%
“…Host cells can utilize different migratory patterns depending on cell morphology, cytoskeletal organization, cell-extracellular matrix interaction, and extracellular stimuli [119]. During migration, the cell is polarized in the direction of motion, possessing leading and trailing edges, blebbing, wide and thin membrane protrusions, the lamellipodium and small finger-like projections, the filopodia.…”
Section: P Aeruginosa 3o-c12-hsl Regulates An Ensemble Of Host Functmentioning
confidence: 99%
“…They can either crawl in the amoeba manner (neutrophils) or move in the mesenchymal mode, utilizing a multistep cycle of protrusion, adhesion, and retraction (fibroblasts, macrophages) [119]. Human neutrophils and macrophages are fast-migrating phagocytes controlling inflammation and infection at the very early contact with bacteria.…”
Section: P Aeruginosa 3o-c12-hsl Regulates An Ensemble Of Host Functmentioning
confidence: 99%
See 1 more Smart Citation